Kesalahan Penggunaan Huruf Kanji Dalam Buku Intermediate Kanji Book Vol. 1 Pada Mahasiswa Semester 3 Angkatan 2016 Program Studi Sastra Jepang FIB UNUD - Artana, Nyoman Rauh (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 1 No 1 (2019), 2019)
This research was conducted to find out the forms of errors made by the 3rd semester 2016 students of Japanese Literature Study Program, Faculty of Cultural Sciences, Udayana University in understanding and using the words with the kanji letters found in the Intermediate Kanji Book Vol. 1. The problems discussed in this study, namely 1) what is the fault of students in understanding and using words with starch in the Intermediate Kanji Book Vol. 1; 2) how to overcome errors in understanding and using words with kanji in the Intermediate Kanji Book Vol. 1. The purpose of this study is to find out the forms of errors made by students in understanding and using words with kanji in the Intermediate Kanji Book Vol. And find a way to overcome these errors. This research is a descriptive qualitative research with documentation method and test method which is continued with note taking technique. The documentation method in this study is a collection of questions that have been filled in with answers by informants. While the test method is an instrument of data collection through a series of questions / exercises distributed to students. The population in this study were all students of the 3rd Semester of the 2016 Class of Japanese Literature Study Program, Faculty of Cultural Sciences Universitas Udayana. The determination of the population is based on the consideration that the 3rd semester 2016 students have been taught material contained in the Intermediate Kanji Book Vol. 1. Through this research, the forms of student errors mentioned above will be able to be broken down and find solutions to overcome them. And the results of this study can be used as teaching materials for lecturers and study materials for students majoring in Japanese literature.